Rancang Bangun Sistem Absensi Menggunakan RFID dan Kamera Berbasis Web (Studi kasus : Gedung BPIW) - Muhammad Fadillah Ilham; Yono Cahyono (CV. Multi Kreasi Media, 2023)
Different companies have different attendance systems. The Regional Infrastructure Development Agency (BPIW) is one part of the PUPR Ministry whose employee attendance system already uses technology, namely the fingerprint attendance system. However, there are still many shortcomings in its use. It is necessary to update the existing employee attendance system by using technology. Based on these problems, the author will create an attendance system using RFID and a web-based camera, which is an object identification method using radio waves. The identification process is carried out by an RFID reader and an RFID transporder (RFID tag). The RFID tag is placed on the employee's id card to be identified. Each RFID tag has a unique identification data number (ID number), so that no RFID tag has the same ID number and its presence data will be identified automatically by the RFID reader and stored in the database, while the ESP-32 CAM is for validation employee attendance, and besides that, in this research, use the Website Interface to provide employee attendance information to personnel and can help to increase effectiveness in processing employee attendance data.